Utilization of bio gas slurry and bio gas slurry enriched with goat’s urine fermented on plant height, leaf production and chemical compositions on Indigofera zollingeriana: - R Arif; N Ginting; I Sembiring (Talenta Publisher, 2019)
The research objective was to examine the utilization of bio gas slurry and bio gasslurry enriched with goat’s urine fermented on Indigofera zollingeriana. The experiment wasconducted at the Goat Farm Research Station Sei Putih, Galang, North Sumatera, from Marchuntil August 2015 using 24 plants of Indigofera zollingeriana. Design experiment was usedsplit plot design where main plots were different dosages of fertilizer, i.e. R1 (75), R2 (150)and R3 (225) ml/plot with four replications. The sub plots were types of fertilizer, i.e. slurry(P1) and slurry and goat’s urine fermented (P2). The research parameters were plant height,leaf production and chemical compositions (rough fat, NDF and ADF).The results showed that dosage fertilizer application of gas slurry and bio gas slurry enrichedwith goat urine fermented was not significantly different to plant height, leaf production andcrude lipid. There was no significantly different on plant height between types of fertilizer, i.e.bio gas slurry and bio gas slurry enriched with goat’s urine fermented. There weresignificantly different (P<0,05) between types of fertilizer, i.e. bio gas slurry and bio gas slurryenriched with goat’s urine fermented on leaf production and chemical compositions. It isconclude that utilization of bio gas slurry enriched with goat’s urine fermented increaseproductivity of Indigofera zolingeriana